Early-life immune activation is a vulnerability factor for adult epileptogenesis in neurofibromatosis type 1 in male mice - Faidi, Rania; Reid, Aylin Y. (Frontiers in Neurology, 2024)
Introduction: Patients with Neurofibromatosis type 1 (NF1), the most common neurocutaneous disorder, can develop several neurological manifestations that include cognitive impairments and epilepsy over their lifetime. It is unclear why certain patients with NF1 develop these conditions while others do not. Early-life immune activation promotes later-life seizure susceptibility, neurocognitive impairments, and leads to spontaneous seizures in some animal models of neurodevelopmental disorders, but the central nervous system immune profile and the enduring consequences of early-life immune activation on the developmental trajectory of the brain in NF1 have not yet been explored. We tested the hypothesis that early-life immune activation promotes the development of spatial memory impairments and epileptogenesis in a mouse model of NF1.Methods: Male wild-type (WT) and Nf1 +/-mice received systemic lipopolysaccharide (LPS) or saline at post-natal day 10 and were assessed in adulthood for learning and memory deficits in the Barnes maze and underwent EEG recordings to look for spontaneous epileptiform abnormalities and susceptibility to challenge with pentylenetetrazole (PTZ).Results: Whereas early-life immune activation by a single injection of LPS acutely elicited a comparable brain cytokine signature in WT and Nf1 +/-mice, it promoted spontaneous seizure activity in adulthood only in the Nf1 +/-mice. Early-life immune activation affected susceptibility to PTZinduced seizures similarly in both WT and Nf1 +/-mice. There was no effect on spatial learning and memory regardless of mouse genotype. Discussion: Our findings suggest second-hit environmental events such as early-life immune activation may promote epileptogenesis in the Nf1 +/-mouse and may be a risk-factor for NF1-associated epilepsy.